Modified Project-Based Learning in Geography: A Better Approach - Firda Islamaya Farhan; Ardimansyah Ardimansyah (FOUNDASIA, 2022)
To ensure students understand the material being studied, constructive and interactive learning is needed. The lack of knowledge about maps and the idea of space among students of Muhammadiyah 1 High School Pontianak causes their inability to understand texts that use maps as the driving force for this research. To work around this, project-based learning is constructive and exciting. Project-based learning is modified and integrated with intensive guidance by the teacher and the division of tasks for each regular group member to ensure all students are active in project completion. Classroom Action Research Methods are used to determine the effectiveness of modified project-based learning. The findings of this study indicate an increase in learning outcomes after implementing Modified Project Based Learning in allocating mining resources in Indonesia through the use of pre-test and post-test. For content to be understood, student-centred learning motivates students to engage in active learning and finally have a good understanding of the content.Keywords: Modified Project Based Learning, Student’s Engagement, Geography